Additive genetic variance and effects of inbreeding, sex and age on heterophil to lymphocyte ratio in song sparrows. (19th November 2015) - Losdat, Sylvain; Arcese, Peter; Sampson, Laura; Villar, Nacho; Reid, Jane M.
Summary: Physiological traits can influence individual fitness and evolutionary changes in stress‐related physiological traits have been hypothesized to mediate the evolution of life‐history traits and trade‐offs. The hypothesis that such physiological variation could drive ongoing life‐history evolution requires non‐zero additive genetic variance in individual stress‐related physiological traits. However, the magnitude of genetic and environmental components of phenotypic variation in stress‐related physiological traits has not been estimated in fully developed vertebrates under natural environmental conditions. We used 490 observations of heterophil to lymphocyte (H : L) ratio, one stress‐related physiological trait, collected from 350 fully developed song sparrows ( Melospiza melodia ) across nine different sampling periods to estimate direct and interacting effects of individual and parental coefficients of inbreeding ( f ), sampling period, age and sex, and to estimate additive genetic variance and heritability. Across all nine sampling periods combined, H : L ratio increased with individual f . However, there was a significant individual f by period interaction whereby H : L ratio increased with individual f in two of the nine sampling periods, hence indicating inbreeding depression. H : L ratio was higher (suggesting an increase in baseline stress level) in older individuals, did not differ between males and females and did not vary with parental f . A quantitative genetic 'animal model' estimated low additive genetic variance in individual H : L ratio. The estimated heritability was h 2  = 0·04 and did not differ significantly from zero. Overall, these results imply that the magnitude of inbreeding depression, as measured through H : L ratio, varies with environmental conditions. In contrast, the low estimated heritability implies relatively low potential for H : L ratio to show an evolutionary response to selection, or hence to mediate the evolution of life‐history trade‐offs. Abstract : Lay Summary